PHARMACOGNOSTIC POTENTIAL FOR MEDICAL APPLICATION OF THE PLANT DRUG JUSTICIA IRWINII WASS. (ACANTHACEAE) OCCURRING IN THE CERRADO OF GOIÁS (CIPEEX, 2025)
ADAMS, R. P.; Identification of Essential Oil Components by Gas chromatography/Mass Spectrometry, 4th ed., Allured: Illinois. 2007.COSTA, A.F. Farmacognosia. 3 v. 3. ed. Lisboa: Fundação Calouste Gulbenkian, 2001.GUIMARÃES, L.D.; SANTOS, S.O. Composição Faunística do Cerrado, Biogeografia e Implicações para a Conservação. In: GUIMARÃES, L.D.; SILVA, M.A.D.; ANACLETO, T.C. (Org.). Natureza Viva Cerrado. Goiânia. GO: Editora da UCG. p. 47-90, 2006.MATOS, F. J. A. Introdução à fitoquímica experimental. Focaliza: UFC, n. 128, p. 1988.MATOS, J. M. D.; Matos, M. E. Farmacognosia. Fortaleza: UFC, 1989.VAN DEN DOOL, H.; KRATZ, P. D. J. A.; Generalization of the retention index system including linear temperature programmed gas-liquid partition chromatography. J. Chromatogr. vol.11, p. 463-471. 1963.WASSHAUSEN, D. Acanthaceae (Acanthus familiy). In: SMITH, N., MORI, S. A., HENDERSON, A., STEVENSON. D. W., HEALD, S. V. Flowering plants of the neotropics. p. 3- 7. Princeton University Press, The New York Botanical Garden, 2004.
Keywords: secondary metabolites; phytochemical screening; herbal medicines